Analysis of Tissue Factor Positive Microparticles - Key, Nigel S. (2010)
There has recently been intense interest in the clinical measurement of tissue factor (TF)-positive microparticles (MPs) in clinical disease states. This interest has been driven by the demonstration of an putative role for circulating TF-positive MPs in animal models of thrombus propagation. Both immunological and functional assays for MP-TF have been described. While each approach has its own advantages and drawbacks, neither has yet been truly established as the ‘gold standard’. Heterogeneity of TF-bearing MPs, such as the variable co-expression of surface phosphatidylserine, may determine not only their procoagulant potential, but also additional properties including rate of clearance from the circulation.